Respostas
respondido por:
26
(a-2b).(a+2b).(a-b) = Primeiro resolvemos o produto notável:
(a² - 4b²)(a-b) = Agr usamos a distributiva:
a³ - 4ab² - a³b - 4b³
(a² - 4b²)(a-b) = Agr usamos a distributiva:
a³ - 4ab² - a³b - 4b³
TC2514:
O produto notavel utilizado foi: (a+b)(a-b) = a² - b²
respondido por:
32
(a - 2b) . (a + 2b) . (a - b)
(a² - 4b²) . (a - b)
a² . a - a².b - 4b².a + 4b².b
=> a³ - a²b - 4ab² + 4b³
(a² - 4b²) . (a - b)
a² . a - a².b - 4b².a + 4b².b
=> a³ - a²b - 4ab² + 4b³
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás